The work process of nurses specialists in Rehabilitation Nursing from a marxist view - João Miguel Almeida Ventura-Silva; Maria Manuela Ferreira Pereira da Silva Martins; Letícia Lima Trindade; Olga Maria Pimenta Lopes Ribeiro; Maria Isabel Barbosa Ribeiro; Maria Filomena Passos Teixeira Cardoso (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: the work process of Specialist Nurses in Rehabilitation Nursing focuses on people with needs for Rehabilitation Nursing care, aiming to promote their training, maximization of functionality and independence. In the light of Marxist theory, this dynamic transformation of work, through specific actions, allows these professionals to organize their work, through a method, using instruments to achieve the final product. Objective: to understand the work process of Specialist Nurses in Rehabilitation Nursing in the light of Marx's framework. Methodology: theoretical-reflective study based on Marx's framework and on literature review in databases and legal documents. Data collection took place in February 2021, and thematic analysis was subsequently carried out. Results: three thematic areas emerged - the work object and final product of the work process, elements of the work process and dimensions of the work process. Discussion: the support of the work process of Specialist Nurses in Rehabilitation Nursing in Marx's framework shows significant contributions to the understanding of the organization of these professionals' work and the factors that may influence it, allowing for a safe and quality professional exercise. Conclusion: the theoretical-reflective analysis of the work process of these professionals confirms the person with rehabilitation care needs as the object of these nurses' work, their role in assisting, managing, investigating, educating and acting politically, with working conditions marking the facilities or difficulties in achieving the purpose of their work.